Enhancing plea bargaining process through mediation - Ab Aziz, Norjihan; Mohamad Amin, Noor Shuhadawati; Ab Hamid, Zuraini (International Organization Center of Academic Research (OCERINT), 2017)
Plea bargaining is an out of court process which allows the accused to plea for reduction of a charge or sentence for an offence that he had committed. It is a common practice among the accused and the prosecutor to expedite the disposal of criminal case. It benefits the prosecutor to secure the punishment of the accused without proceeding to a full trial, which needs a certain procedure and a higher standard of proof to prove the accused guilty of an offence. Through plea bargaining, the accused will not be subjected to severe charge or punishment, and the prosecutor and the accused cannot appeal the case to the higher court if plea bargaining is successful. Nevertheless, the process of negotiation without the assistance of a third party could lead to the unsuccessful of plea bargaining which may result to a full trial. This happens if the prosecutor or the accused disagree with the sentence or a new charge offered by any one of them. This will cause inconvenience to the accused if he initially agrees to plea bargaining for reduction of the charge or sentence, however, due to the dissatisfaction of the suggestion of a new charge or sentence offered by the accused, the prosecutor tends to proceed the case to a full trial. This can be avoided if a neutral third party assists the accused and the offender to reach a deal. For instance, in Singapore a judge acts as a mediator to facilitate the process of plea bargaining to resolve criminal cases out of court. Thus, this research examines how plea bargaining is conducted under the Criminal Procedure Code of Malaysia. It also analyses how mediation helps plea bargaining process under the law of Singapore. It is suggested that the Criminal Procedure Code of Malaysia be amended to allow a third party to facilitate the process of plea bargaining.